Question

(3t−7)(1+3t^2)

Probability and combinatorics
ANSWERED
asked 2021-06-01
\(\displaystyle{\left({3}{t}−{7}\right)}{\left({1}+{3}{t}^{{2}}\right)}\)

Answers (1)

2021-06-02
We are given: \(\displaystyle{\left({3}{t}−{7}\right)}{\left({1}+{3}{t}^{{2}}\right)}\)
Apply distributive property: a(b+c)=ab+ac \(\displaystyle={\left({3}{t}-{7}\right)}{1}+{\left({3}{t}-{7}\right)}{3}{t}^{{2}}\) \(\displaystyle={3}{t}-{7}+{9}{t}^{{3}}-{21}{t}^{{2}}\) or \(\displaystyle={9}{t}^{{3}}-{21}{t}^{{2}}+{3}{t}-{7}\)
0
 
Best answer

expert advice

Need a better answer?
...